2022
DOI: 10.3390/ijerph19073887
|View full text |Cite
|
Sign up to set email alerts
|

Promoting COVID-19 Vaccination Using the Health Belief Model: Does Information Acquisition from Divergent Sources Make a Difference?

Abstract: As a promising approach to stop the escalation of the pandemic, COVID-19 vaccine promotion is becoming a challenging task for authorities worldwide. The purpose of this study was to identify the effective sources for disseminating information on the COVID-19 vaccine to promote individuals’ behavioral intention to take the vaccine. Based on the Health Belief Model (HBM), this study illustrated the mechanism of how COVID-19 information acquisition from different sources was transformed into vaccination intention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 78 publications
2
9
0
Order By: Relevance
“…Only concerns about new variants of the COVID-19 virus were associated with COVID-19 vaccination status when demographic and general vaccine beliefs were included in the model. It should be noted, however, that some published studies, such as that of Yang et al, 2022, found that components of the Health Belief Model, which places emphasis on risk-benefit perceptions, perceived barriers, and cues to action, have found some associations with COVID-19 vaccination (e.g., perceived benefits, information sources used) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only concerns about new variants of the COVID-19 virus were associated with COVID-19 vaccination status when demographic and general vaccine beliefs were included in the model. It should be noted, however, that some published studies, such as that of Yang et al, 2022, found that components of the Health Belief Model, which places emphasis on risk-benefit perceptions, perceived barriers, and cues to action, have found some associations with COVID-19 vaccination (e.g., perceived benefits, information sources used) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the establishment of appropriate health beliefs are the prerequisite for cues to action to prompt a health behaviour (Rosenstock, 1966 ), the popularisation of HPV related knowledge should be valued. Previous studies have shown that social media is more influential in promoting an individual’s health beliefs than traditional media (Yang et al, 2022 ). Therefore, the social media can be a crucial channel to reshape the promotion of HPV vaccination, by emphasising more on learning adequate and accurate HPV knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of health communication, the theoretical construct of HBM has been widely used to examine media coverage of health-related behaviour and benefit the design of health education campaigns (Kim, 2018 ; Zhang et al, 2017 ). The HBM has been designed specifically for understanding those people who were attempting to act to ameliorate their well-being conditions as a healthy manner to prevent a negative health result (Wong et al, 2020 ; Yang et al, 2022 ). Previous studies have used HBM to examine the public perception and knowledge of health-related behaviour on social media platforms (Briones et al, 2012 ; Massey et al, 2020 ; Yoo et al, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the case of the COVID-19 vaccine, new information about side effects and growing doubts about its efficacy may discourage people from using it. 10 On the other hand, perceived benefits were found to be the most powerful predictor of all health belief components in a meta-analysis of HBM research. 11 The relevance of public awareness of infection risk, vaccine safety, and the necessity and safety of maternal vaccination is emphasized.…”
Section: Discussionmentioning
confidence: 95%